THE REGISTER ANALYSIS OF “BEING THERE MOVIE” - Muhammad Ari Saputra (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2022)
This study describes of register in being there movie. The purpose of this study was to analysis of register in being there movie and using communication events include three things, namely area (field), atmosphere (tenor), and method (mode). This study will help teachers and lecturers understand the communication each others in the teaching process, as well as how students feel in the classroom.This study used descriptive method with a qualitative approach. The focus of this study was on register, field, tenor and mode in being there movie. In hybrid learning, ten data points of facial expression were identified. The data register because the meaning of register itself is occupational style using specialized or technical jargon, It refers to the language of groups of people who share common interests or jobs, or the language used in situations involving such groups, such as the language of doctors, engineers, journals, legalese, and so on. The findings of this study show that Register has different name that is ‘context of situation’. It has three dimension points; those are tenor, field and mode. Field is concerned with the communication's purpose and subject matter; Mode is concerned with the means of communication, most notably speech or writing; and Tenor is affected by the relationships between participants.